Analysis of Risk Factors and Establishment of a Prediction Model for Endoscopic Primary Bile Reflux: A Single-Center Retrospective Study - Chen, Li; Zhu, Guoying; She, Ling; Ding, Yongnian; Yang, Changqing; Zhu, Fengshang (Frontiers in Medicine, 2021)
Background: Endoscopic primary bile reflux (EPBR) is one of the main diagnostic criteria for bile reflux gastritis (BRG). It is presently not clear that the risk factors and prediction models of EPBR in gastropathy patients who cannot or will not undergo endoscopy due to contraindications. This study aimed to evaluate the risk factors of EPBR and to establish and verify a prediction model. Methods: A series of 844 patients (564 subjects with EPBR and 280 control subjects) were retrospectively selected for this study and divided into a training set (n=591) and a validation set (n=253) according to the usual ratio of 70%:30% for subsequent internal validation of the logistic regression model for EPBR. Fourteen parameters that might affect the occurrence of EPBR were collected. Subsequently, the univariate and stepwise logistic regression analyses were introduced to reveal the risk factors and the multivariate prediction model. An R package was dedicated to the corresponding internal validation of the EPBR model. Results: Univariate analysis showed that gender, age, smoking, Helicobacter pylori (H.pylori) infection status, metabolic syndrome(MS), non-steroidal anti-inflammatory drugs(NSAIDs) use history, and previous medical histories of chronic liver diseases, cholelithiasis, and erosive gastritis were statistically significant between the two groups (P<0.05). Multivariate regression described that male[OR(95%confidence interval, CI)=2.29(1.50–3.50), P<0.001], age≥45 years old [OR(95%CI) =4.24 (2.59– 6.96), P<0.001], H. pylori infection status [OR(95%CI)=2.34(1.37–4.01), P=0.002], MS [OR(95%CI) =3.14(1.77–5.54), P<0.001], NSAIDs use history [OR (95% CI) =1.87 (1.03–3.40), P=0.04], cholelithiasis history[OR(95%CI)=3.95(2.18–7.18), P< 0.001] and erosive gastritis history[ [OR(95%CI) =6.77(3.73–12.29), P<0.001] were the risk factors for the occurrence of EPBR. Based on the results of these risk factors, an EPBR prediction model with adequate calibration and excellent discrimination was established (AUC: 0.839, 95% CI=0.806–0.872). Conclusions: Male, age≥45 years old, H.pylori infection, histories of MS, NSAIDs use, cholelithiasis, and erosive gastritis appear to be the risk factors for EPBR, and our favorable prediction model might be an option for the prediction of EPBR.